Efektivitas Kandungan Bahan Aktif Agen Anti Plak Gigi Komersial Terhadap Penurunan Plak Gigi - Nur Ariska Nugrahani (Faculty of Medicine, Universitas Andalas, 2021)
Yellowish plaque on the teeth can cause tartar and caries until causing swollen gums. Objective: To compare the antibacterial effect on plaque reduction of toothpaste containing zinc-citrate, fluoride, sodium monofluorophosphate. Methods: This study uses a pretest-post-test control group design with 20 participants aged 16-23 years through a zoom meeting, the calculation of the Oleary Index which is categorized as good (score 0-20%), moderate (score 21-40%), poor (score 41-60%) and very bad (score > 60%). Results: In group A, using 1.12% sodium monofluorophosphate and 2% calcium carbonate showed that most of the study participants showed a decrease in plaque in the second week. Group B using 5% Pyrophosphate and 0.3% sodium fluoride experienced a decrease in plaque index in the second week, the calculation of the O'Leary plaque index, especially in study participants B5 who experienced a significant decrease in plaque index. In group C, using 5% pyrophosphate, 0.2% sodium fluoride and 0.2% zinc citrate. experienced a decrease in plaque index in the second week, but with a less significant difference in the percentage of plaque index. Conclusion: The index decreased significantly in group B toothpaste containing plaque agents in the form of pyrophosphate and 0.3% sodium fluoride.